Buah Kemas.ID of E-Commerce Performance Platform for Agricultural Product Sales on CV. Wirabhumi Mandiri - Rossyda Priyadarshini; Tri Murjoko; Wahyu Santoso (Nusantara Science and Technology Proceedings)
CV. Wirabhumi Mandiri is one of the private businesses that carries out agribusiness efforts on food crops, plantations and fisheries, as well as conducting general trading and export trade, inter - island interiors, distributors of agricultural products including the sale of agricultural production facilities. UPN “Veteran” of East Java Team comes through a series of technological innovation proposals to provide solutions on marketing and sales issues faced in the form of e-commerce web creation from a business process perspective towards transaction automation and enterprise workflow, also increasing the sales and purchase capacity of products and information on-line. System approach is a problem assessment method that begins with an analysis or identification of needs that will result in an efficient operational system. The e-commerce program will be implemented using SDLC (System Development Life Cycle) approach with the Waterfall method. BuahKemas.id are e-commerce applications for partner companies provide some advantages such as increased market exposure, lowering operating costs, shortening the product cycle time, improving supplier management, expanding market reach (global reach market) and increasing customer loyalty.